2011
DOI: 10.14710/jitaa.36.4.221-227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Polymorphism of FSH Beta-Subunit Gene as Sperm Quality Marker in Bali Cattle Using PCR-RFLP

Abstract: Penelitian dilakukan untuk mengidentifikasi keragaman gen FSH beta-subunit dengan metode PCR-RFLP sebagai penanda kualitas sperma pada sapi Bali. Pengambilan sampel darah untuk ekstraksi DNA dari berbagai populasi sebanyak 470 sampel dan 127 sampel yang berasal dari Balai Nasional Inseminasi Buatan dan Balai Inseminasi Buatan Regional beserta data sperma. Frekuensi alel pada sapi Bali adalah alel A (0,000) dan alel B (1,000). Tidak ditemukannya alel A menunjukkan gen FSH betasubunit pada sapi Bali bersifat mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
3
0
3
Order By: Relevance
“…Such differences in SNPs and their frequency in different species and/or breeds were reported in previous studies. Ishak et al (2011) reported the FSHβ3-a SNP in five cattle breeds, Bali, Brahman, Simmental, Limousine, and Holstein. They observed Bali cattle to be monomorphic for this locus.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in SNPs and their frequency in different species and/or breeds were reported in previous studies. Ishak et al (2011) reported the FSHβ3-a SNP in five cattle breeds, Bali, Brahman, Simmental, Limousine, and Holstein. They observed Bali cattle to be monomorphic for this locus.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hardy-Weinberg Equilibrium (HWE) was calculated directly using formula (Noor, 2008;Ishak et al, 2011):…”
Section: Discussionmentioning
confidence: 99%
“…Zulkarnain (2010) suggested that the growth hormone receptor gene (GRH/Alul1) in Bali cattle was monomorphic. Furthermore, Ishak et al (2011) Ciamis local cattle population and PO cattle, were 0.449, 0.571 and 0.382, 0.440, respectively (Table 2). The heterozygosities value were a medium category.…”
Section: Scd1 Gene Variationmentioning
confidence: 98%